Does family ownership and women leadership influence sharia bank financial performance? - Rahman Anshari; Dewi Sartika (INOVASI, 2022)
This study empirically examines the effect of family ownership and women's leadership on company boards on the financial performance of Islamic banks. This research is quantitative. Data were obtained from the annual report of Islamic Commercial Banks in 2014-2020. The sample was selected using a purposive sampling technique using specific criteria with a total sample of 77 observations for 7 years of research. Family ownership is measured using the size of the family's share in the company. Leadership is calculated using the proportion of women on the company's board (board of commissioners, board of directors, and sharia supervisory board). Financial performance is measured using ROA. Data analysis in this study used multiple regression using the IBM SPSS version 23 application. The results showed that family ownership had a negative effect on the company's financial performance. The female leadership variable has a positive impact on company performance.